Padronização do teste da formalina para avaliar nocicepção em Danio rerio e avaliação do efeito antinociceptivo do extrato bruto de Sinningia warmingii (hiern) chautems - Santos, Wanderson Praxedes (2016)
The pain is an unpleasant feeling, but it is critical to the individual's survival, given its protective function. However, due to their disabling character in certain pathological conditions have been sought effective analgesic drugs with fewer adverse effects. In this context, the plants represent an important source for finding new analgesic molecules. For this the ethnopharmacological research is fundamental. The Sinningia warmingii belonging to Gesneriaceae family is a plant of important traditional use for the treatment of pain in southern and south-east of Brazil However, there are few studies that demonstrate the analgesic efficacy of this plant. Thus, our study proposes the evaluation of the antinociceptive properties of this plant using the zebrafish as an animal model. The behavioral responses of zebrafish induced by subcutaneous injection of formalin in different concentrations in the fish's tail were evaluated using the following parameters: time of freezing (s), permanence time in the tank bottom (s) and distance traveled (cm) which indicate changes in the swimming activity. We observed that 0.1% formalin got better nociceptive response in zebrafish. Furthermore, morphine 3 mg / kg was able to significantly reverse the change in swimming activity induced by formalin 0.1%. The Sinningia warmingii extract (0.3, 1 and 3 mg / kg; ip) also reversed these behaviors dose-dependent manner, confirming its antinociceptive activity indicated by the popular use.